2020
DOI: 10.1007/s11739-020-02412-1
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of comorbidities and 1-year mortality in elderly patients with COPD hospitalized in internal medicine wards: data from the RePoSI Registry

Abstract: Currently, chronic obstructive pulmonary disease (COPD) represents the fourth cause of death worldwide with significant economic burden. Comorbidities increase in number and severity with age and are identified as important determinants that influence the prognosis. In this observational study, we retrospectively analyzed data collected from the RePoSI register. We aimed to investigate comorbidities and outcomes in a cohort of hospitalized elderly patients with the clinical diagnosis of COPD. Socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
1
10
0
2
Order By: Relevance
“…RePoSi is an independent and collaborative registry, organized by the Italian Society of Internal Medicine (SIMI), IRCCS Ca’ Granda Maggiore Policlinico Hospital Foundation, and the Mario Negri Institute for Pharmacological Research, that was made up to recruit, monitor, and evaluate hospitalized older adults ≥65 years admitted to 102 Italian internal medicine and geriatric wards, with data coming from each single medical record, and collected every 2 years from 2008. The project’s design has been previously described in detail [ 10 ]. Briefly, patients were eligible for RePoSi if: (1) they were admitted to one of the participating regional internal medicine wards during the four index weeks chosen for recruitment (one in February, one in June, one in September, and one in December); (2) their age was 65 years or older; (3) they gave informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RePoSi is an independent and collaborative registry, organized by the Italian Society of Internal Medicine (SIMI), IRCCS Ca’ Granda Maggiore Policlinico Hospital Foundation, and the Mario Negri Institute for Pharmacological Research, that was made up to recruit, monitor, and evaluate hospitalized older adults ≥65 years admitted to 102 Italian internal medicine and geriatric wards, with data coming from each single medical record, and collected every 2 years from 2008. The project’s design has been previously described in detail [ 10 ]. Briefly, patients were eligible for RePoSi if: (1) they were admitted to one of the participating regional internal medicine wards during the four index weeks chosen for recruitment (one in February, one in June, one in September, and one in December); (2) their age was 65 years or older; (3) they gave informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…About 60% of elderly subjects with diabetes have one comorbidity, whereas 40% have four or more comorbid chronic conditions [ 7 ]. We previously published data from the RePoSi registry that evidenced clinical impact of comorbidities according to gender differences [ 8 , 9 ] and different diseases in the elderly population hospitalized in internal medicine and geriatric Italian wards [ 10 , 11 ]. Recently, we showed that one of the stronger predictors of in-hospital mortality for older patients admitted in general wards was a glycemia level ≥250 mg/dL [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to frailty, a cluster of clinical and demographic factors including age and sex is associated with poor prognosis and mortality in elderly patients [7][8][9][10][11][12]. Although studies demonstrated an increased prognostic value of MPI according to sex and older age [13,14], at present these factors are not included in this tool.…”
Section: Introductionmentioning
confidence: 99%
“…An observational retrospective study was carried out using the REgistro POliterapie SIMI (REPOSI) database and considering all data collected from January 2010 to December 2016. The REPOSI is a multicenter collaborative observational registry cooperatively established by the Italian Society of Internal Medicine (SIMI), IRCCS Ca' Granda Maggiore Policlinico Hospital Foundation and Mario Negri Institute of Pharmacological Research IRCCS that was made up to recruit, monitor and evaluate hospitalized older adults ≥65 years admitted to 102 Italian internal medicine and geriatric wards with data came from each single medical record and collected every 2 years from 2008 onwards (Nobili et al, 2011;Argano et al, 2020). The study protocol was approved by the local Ethics Committee of the responsible hospitals, and the creation of a database was conducted according to Good Clinical Practice recommendations and the Declaration of Helsinki while maintaining the anonymity of patients.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%